Boarding schools: A longitudinal examination of Australian Indigenous and non‐Indigenous boarders' and non‐boarders' wellbeing. (26th March 2022) - Dillon, Anthony; Craven, Rhonda G.; Guo, Jiesi; Yeung, Alexander S.; Mooney, Janet; Franklin, Alicia; Brockman, Rob
Abstract: Improving educational outcomes for Indigenous Australian students is a key strategy to helping Indigenous people reach their full potential. This has resulted in well‐intentioned efforts by Australian educators and governments to ensure Indigenous children have positive school experiences. However, Indigenous students still lag behind their non‐Indigenous counterparts in educational outcomes. This is particularly so for Indigenous students living in rural and remote parts of Australia where educational opportunities are limited, especially in high school. One solution to this problem has been to enrol these students in boarding schools in urban and metropolitan centres. While research on the success of boarding schools for Indigenous students is scarce, what little that does exist is not encouraging. The focus of this research was to examine the effects of boarding for Indigenous ( n = 11) and non‐Indigenous students' ( n = 158) wellbeing ( N = 1423) in two large private boys' schools. Participating students aged 12–18 years old completed a survey measuring wellbeing constructs on two occasions, 12 months apart. Non‐Indigenous boys were generally higher in wellbeing compared with Indigenous boys. There was also evidence of improved social wellbeing beyond that of non‐Indigenous boarders over time. Overall, while evidence of merit was weak, boarding schools may benefit their Indigenous students' development in social wellbeing.